2013
DOI: 10.1371/journal.pone.0083522
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Substantivity on Salivary Flora and Plaque-Like Biofilm: An In Situ Model

Abstract: ObjectiveTo evaluate the in situ antibacterial activity of a mouthrinse with 0.2% Chlorhexidine (M-0.2% CHX) on undisturbed de novo plaque-like biofilm (PL-biofilm) and on salivary flora up to 7 hours after its application.MethodsA special acrylic appliance was designed, with 3 inserted glass disks on each buccal side, allowing for PL-biofilm growth. Fifteen healthy volunteers wore the appliance for 48 hours and then performed an M-0.2% CHX; disks were removed at 30 seconds and 1, 3, 5 and 7 hours after the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
41
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 43 publications
14
41
1
2
Order By: Relevance
“…6 The action of CHX on the membrane structure permits the use of fluorescence staining techniques based on combinations of dyes, which can differentiate vital from non-vital cells due to membrane permeability and integrity. A common combination used in studies on the activity of antimicrobial agents both on dental plaque 7,8 and on salivary microbiota [7][8][9][10][11][12] has been found in the LIVE/DEAD 1 BacLight TM Viability Kit (Molecular Probes, Leiden, The Netherlands), which is composed of Syto 9 and propidium iodide. Their staining principle is simple, as both are based on membrane permeability; Syto 9 penetrates all vital and non-vital cells due to its ability to penetrate intact cells, while propidium iodide only penetrates those cells with higher cell membrane permeability (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The action of CHX on the membrane structure permits the use of fluorescence staining techniques based on combinations of dyes, which can differentiate vital from non-vital cells due to membrane permeability and integrity. A common combination used in studies on the activity of antimicrobial agents both on dental plaque 7,8 and on salivary microbiota [7][8][9][10][11][12] has been found in the LIVE/DEAD 1 BacLight TM Viability Kit (Molecular Probes, Leiden, The Netherlands), which is composed of Syto 9 and propidium iodide. Their staining principle is simple, as both are based on membrane permeability; Syto 9 penetrates all vital and non-vital cells due to its ability to penetrate intact cells, while propidium iodide only penetrates those cells with higher cell membrane permeability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The first, can give information on the mechanism standpoint such as minimum inhibitory concentration or bacterial kill-time curves, but give very limited clinical perspective on a so dynamic ecosystem like the oral cavity. On the other hand, in vivo models vary from methods based on plaque re-growth assessments on short periods of time 17 or others using saliva [8][9][10]12,18,19 and/or dental plaque after a single application. [19][20][21] Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, this variable has not been evaluated, with studies found in which the volunteers did not brush their teeth at all [50,51], while there are others in which they did [79,52,53]. Our results revealed that the thickness of the SF-biofilm formed after 48 h and its bacterial viability were significantly affected by the toothbrushing protocol, as these microscopic parameters were higher in test 1 (without toothbrushing), especially in the medial-mesial positions.…”
Section: Discussionmentioning
confidence: 99%
“…CHX widely used antimicrobial in Dentistry [18], due to it is strong antibacterial activity and ability to reduce the accumulation of oral biolms [19]. Its efficacy can be attributed to bactericidal and substantivity effects [20], broad spectrum against microorganism, both aerobic and anaerobic, and selectively suppress the growth of caries-associated S. mutans [21]. CHX presents antimicrobial efficacy in vitro and in vivo (mouthwash) against salivary microbiota cariogenic and has a role in preventing the development of gingivitis [22].…”
Section: Discussionmentioning
confidence: 99%